Association of food insecurity with dietary patterns and expenditure on food, alcohol and tobacco amongst indigenous Inuit in Greenland: results from a population health survey - Peter Bjerregaard; Ingelise Olesen; Christina Viskum Lytken Larsen (BMC, 2021)
Abstract Background Amongst the indigenous Greenlandic Inuit, the experience of food insecurity has been attributed to a lack of money to buy enough food of sufficient quality to sustain a family, although a preference for alcohol and tobacco over food has also been cited. The purpose of the article was to compare dietary patterns and expenditure on food, alcoholic beverages and tobacco between survey participants who reported food insecurity and those who did not. Methods A countrywide cross-sectional health survey was carried out among 1886 adult Greenlandic Inuit in 2018. Diet was estimated by a food frequency questionnaire. Food insecurity status was based on the household hunger scale. Analyses were carried out by univariate general linear models adjusted for age, sex and social position. Results Nine percent of the participants reported food insecurity. Food insecurity was higher among younger participants, men and participants with low social position. Food insecure participants more often chose an unhealthy dietary pattern (43% vs. 32%) and they reported a higher energy intake. The food insecure spent the same amount of money on food as other participants but less on nutritious food and more on non-nutritious food. The cost per kilojoule (kJ) of the food of the food insecure was lower than that of the food secure (DKK 8.0 and 9.0 per 1000 kJ, respectively). The food insecure participants also spent considerably more on alcohol and tobacco. Conclusions The results suggest that it is not only unemployment and lack of money that creates food insecurity and unhealthy dietary patterns in Greenland. Food insecure participants gave higher priority to buying non-nutritious food, alcohol and tobacco than did food secure participants. There seems to be at least two population subgroups in Greenland with poverty and substance use, respectively, as the immediate determinants for food insecurity. The results are important for the design of interventions against food insecurity and unhealthy dietary patterns.